Penerapan Cara Belajar Menggunakan Media TikTok dengan Upaya Peningkatan Daya Tanggap pada Materi Genetika Manusia terhadap Siswa-siswi MAN I Labuhanbatu Utara - Wella Aulinda Dalimunthe; Risma Delima Harahap; Rosmidah Hasibuan (CV. Global Cendekia Inti, 2026)
In improving students' responsiveness in learning, using media that can encourage students' curiosity is very important to do, the higher the curiosity, the higher the students' ability to grasp the material given, at MAN I Labuhanbatu Utara, the understanding of human genetics material is still not fully understood by students. Genetics is a branch of biology that studies the inheritance of traits from one generation to the next. This science has developed rapidly since the discovery of the laws of heredity by Gregor Mendel in the 19th century. As technology advances, understanding of DNA structure, gene expression, and genetic engineering has opened up various applications in medicine, agriculture, and biotechnology. The research sample was 35 students of MAN I, the results of the Levene test showed that the assumption of homogeneity of variance had met the homogeneity criteria (sig> 0.05). So it can be concluded that the test has been met well. The test result for time management was 7.569, with a t-table value of 2.042 (t-count > t-table), with a significance value of 0.000 < 0.05. Therefore, H0 is rejected and H0 is accepted. The results show that the calculated f-value is greater than the f-table value (57.287 > 3.32), with a significance value of 0.000 less than 0.005. The results indicate that all independent variables collectively influence the dependent variable.